Covax must go beyond proportional allocation of covid vaccines to ensure fair and equitable access. (5th January 2021) - Herzog, Lisa M; Norheim, Ole F; Emanuel, Ezekiel J; McCoy, Matthew S
Abstract : International collaboration is key for the fair and efficient distribution of covid-19 vaccines. Lisa Herzog and colleagues ' Fair Priority Model, with its focus on allocating vaccine based on limiting covid-19 harms, realises ethical principles better than Covax's proposal of proportional allocation based on population